Eksplorasi Teknik Tapestri dan Pewarnaan Serat Lidah Mertua untuk Bahan Alternatif Aksesoris Fesyen - Rinta Tri Anjani; Bayyinah Nurrul Haq; Yunita Fitra Andriana (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
About 60% of synthetic fabric fibers are used in fashion products that threaten theenvironment because they are difficult to decompose. The exigent condition of the accumulationof waste that does not decompose requires innovation of environmentally friendly materials forthe fashion industry. Therefore, to support the use of environmentally friendly materials, thisstudy explores the fibers of the Sanseivera sp. The superiority of the in-laws' tongue fiber is that ithas long fibers, is easy to twist and weave, and is easy to color with natural dyes. The explorationincludes processing techniques, namely macramé, tapestry, and other additive exploration;Exploration of the coloring used with natural dyes, namely Secang, Teger, Mango leaves,Avocado, Purple sweet potato, and Mangosteen; and application of exploration results intofashion accessories products. The result is an ideal tapestry technique for the exploration processof fiber materials. Additional materials to strengthen the fiber braid are latex and starch pulp. Theexploration of coloring with natural dyes resulted in the Hard - Soft - Warm color range of theKobayashi color matrix. Exploration application by making bags made of canvas, wovenmaterial as a result of technical exploration and coloring is affixed with the squeeze sewingtechnique.